Iterative evaluation of a virtual three-dimensional environment for start-up entrepreneurship in different application scenarios - Pirker, J,; Guetl, Christian (IEEE, 2012)
The Virtual Incubator World (VIW) is a virtual three-dimensional learning environment developed in Open Wonderland and is designed to support start-up entrepreneurs during the phases of knowledge acquisition, establishment of social networks and business idea exploitation. Therefore this environment is designed to support functionalities such as collaborative activities, possibilities to train key competences, resource provision but also role playing games. A helpful, motivational and friendly environment is the objective to be provided to the students, which supports different application scenarios and provides a collaborative solution for not only start-up entrepreneurs but also for different target groups. Intention of the virtual world is to enhance learning activities in entrepreneurial courses, help start-up entrepreneurs in the beginning and also in the promotional phase and should facilitate the business incubator’s activities. This paper introduces the different VIW branches designed for the needs of those different person groups, points out the different requirements and focuses on the evaluation of the defined application scenarios. According previous studies the major problems were defined as security, technical and acceptance issues. Due to iterative evaluations the VIW and according scenarios were improved to enhance in particular the users’ acceptance of the novel e-learning and collaboration possibility by pointing out the advantages in comparison to conventional e-learning tools. Also technical issues were minimized by establishing exhaustive instructions and tutorials.